PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP RELATIONSHIP QUALITY (RQ) DI RSUD ABDUL WAHAB SJAHRANIE - Sumarni, Sumarni; Adrianto, Ratno; AR, Chaerunnisa; Rahayu, Eka Putri (Jurnal Manajemen Kesehatan Indonesia, 2025)
This study analyzes the influence of Customer Relationship Management (CRM) on Relationship Quality (RQ) in inpatient services at Abdul Wahab Sjahranie Regional Public Hospital, Samarinda. CRM in healthcare comprises four dimensions: Customer Knowledge, Customer Knowledge Management Capability, Customer Interaction, and Customization, which theoretically support patient trust, satisfaction, and commitment. Using a quantitative analytical survey design, data were collected from 390 purposively selected inpatients who had visited the hospital at least twice in the past six months. A closed-ended Likert scale questionnaire was used, and data were analyzed with the Chi-square test. Results show that Customer Knowledge, Customer Knowledge Management Capability, and Customization significantly affect RQ, while Customer Interaction has no significant effect. These findings highlight that understanding patients comprehensively, effectively managing patient knowledge, and tailoring services to patient needs are strategic in strengthening hospital–patient relationships. Practical implications suggest prioritizing CRM strategies focused on patient needs and experiences to foster long-term, mutually beneficial relationships.